The heparin-like activities of negatively charged derivatives of low-molecular-weight polymannuronate and polyguluronate. (2nd January 2017) - Li, Quancai; Zeng, Yangyang; Wang, Linlin; Guan, Huashi; Li, Chunxia; Zhang, Lijuan
Highlights: LPM and LPG were prepared from alginate and studied side-by-side. LPM and LPG derivatives containing −PO3 2−, −PO2 H − and −SO3 − were synthesized. SO3 − modification of LPM and LPG enhanced the anticoagulant and FGFs/FGFR1c signaling activation activities. Sulfated LPG had better heparin-like activities than sulfated LPM. Abstract: A series of low-molecular-weight polymannuronate (LPM) and polyguluronate (LPG) polyanionic derivatives, including LPM/LPG phosphate (LPMP/LPGP), LPM/LPG H-phosphonate (LPMHP/LPGHP) and LPM/LPG sulfate (LPMS/LPGS), were prepared as heparinoids by chemical modification of LPM and LPG. The structures and characteristics of LPM, LPG and their derivatives were elucidated based on high performance gel permeation chromatography (HPGPC), fourier transform infrared spectroscopy (FT-IR), nuclear magnetic resonance spectroscopy (NMR) and polyacrylamide gel electrophoresis (PAGE). In order to test the heparin-like activities of these derivatives and to reveal the activities affected by substituent groups and PM/PG polysaccharide backbones, the anticoagulant activities and FGF/FGFR1c signaling activation abilities were evaluated in vitro . The results showed that sulfate group was the best substituent group to improve the heparin-like activities of LPM/LPG compared with the other two anionic groups. The results also showed that sulfated derivative based on PG structure had better activities than that based on PM structure.